PRODUKTIVITAS ANGKUT TRUK DAN TRUK SEMI-TRAILER - Apul Sianturi; Djaban Tinambunan (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
An investigation on log hauling by truck and semi-trailer truck has been carried out at 14 concession areas in Sumatera and 5 concession areas in South Kalimantan in 1980 and 1981. The investigation comes to the following conclussions :1. Logging Companies in Riau, Jambi and South Sumatera use poorly constructed forest roads without any graveling.2. On the other hand those in South Kalimantan are relatively good graveled roads.3. Effective hauling outputs of trucks range from 91 to 361 m3km/round trip hour, with an average of 247 m3 km/round trip hour, and those of semi-trailer truck from 265 to 841 m3 km/round trip hour, with an average of 494 m3 km/round trip hour.There is pronounced linier relation between hauling distance and round trip time.